Temporal and kinematic analyses of timed up and go test in chronic low back pain patients - Buraschi, Riccardo; Pollet, Joel; Villafañe, Jorge Hugo; Piovanelli, Barbara; Negrini, Stefano (Gait & posture, 2022)
To analyze temporal and kinematic parameters of chronic Low-Back Pain (cLBP) subjects compared to healthy subjects during Timed Up and Go Test (TUG) execution implemented with an Inertial Measurement Unit and to explore the correlations of those parameters with pain and disability. Observational cross-sectional study. Thirty-one subjects with cLBP [(19 females - 61%), mean age 61 ± 19] were allocated to the case group, and 14 healthy [(10 females - 71%), mean age 62 ± 6] subjects to the control group. Instrumented TUG was administered to both groups. The Roland Morris Disability Questionnaire and Numerical Pain Rating Scale (NPRS) were also administered for disability and pain assessment in the case group. Mean TUG time to completion [12.2 ± 3.5 s for cLBP; 8.1 ± 0.9 s for healthy] and the most of sub-phases duration significantly differed between groups (p < 0.05). As for kinematic parameters, significant differences (p < 0.05) were mainly retrieved in acceleration components during the sit-to-stand and stand-to-sit phase, with the cLBP group showing lower accelerations. Significant correlation [from strong (ρ = 0.75 of time to completion) to moderate (ρ = 0.43 of sit-to-stand)] was observed between RMQD score and all temporal parameters and with most of the kinematic parameters. No correlation with NPRS score was found. Instrumented TUG application into a cLBP population provides valuable information about movement behaviors with a deeper assessment of objective functional impairment and disability in respect of the classical stop-watch outcome of TUG, possibly allowing a better design of the rehabilitative intervention. •Chronic Low Back Pain brings kinematic alterations of movement.•Disability is correlated to temporal parameters alteration of Timed Up and Go test.•Instrumented Timed Up and Go test provides valuable information on movement.